FAO/IBPGR technical guidelines for the safe movement of musa germplasm (2nd edition) - Diekmann, M.; Putter, C.A.J.; Food and Agriculture Organization of the United Nations (1996)
These guidelines are divided into 2 parts. The first makes general recommendations on how best to move Musa germplasm, technical protocols and seed treatment. The second part covers 5 important virus diseases of quarantine concern (abaca mosaic potyvirus, banana bract mosaic potyvirus, banana bunchy top nanavirus, banana mosaic (cucumber mosaic cucumovirus) and banana streak badnavirus). The information given on any particular pathogen concentrates on those aspects most relevant to quarantine. (Abstract © CAB ABSTRACTS, CAB International)